Initial assessment of runoff quality from a road and highway in Klang Valley - Salleh, Md Noor; Al-Mamun, Abdullah; Muyibi, Suleyman Aremu; Zainudin, Zaki; Idris , Azni; Abdul Latiff , Nurzuliana; Suhaimi, Ahmad Safiuddin (2013)
Primary data is being collected to study the quality of storm runoff produced from the road surfaces in Klang Valley. Seven locations at various tolled highways and one location at IIUM are selected for the collection of primary data on storm runoff quality. As many as 20 various relevant water quality parameters, consisting the major groups of pollutants, are chosen to be tested for runoff quality from the selected road and highways. Event Mean Concentration (EMC) is being calculated to compare the runoff quality from various roads. However, not all pollutants are tested yet. This paper presents results of runoff quality from a road selected at IIUM and nearby MTD toll on Kuantan highway. According to the initial evaluation, EMC value for COD of the highway runoff (73 mg/L) is higher than that of local road runoff (44 mg/L). On the other hand, the TSS of the road runoff (273.5 mg/L) is higher than that of highway (215 mg/L). When compared to Class II of the National Water Quality Standard (NWQS), it was observed that the runoff from the roads and highways are inferior with respect to BOD, COD, TSS and Turbidity, indicating road runoff must be treated before discharged into the river system. It is expected that completion of the study would provide some baseline EMC values for the highways in the Klang Valley.